Pengaruh Keterampilan Komunikasi terhadap Hasil Belajar Menggunakan Metode Diskusi pada Materi Asam Basa - Ahmad Abidin; Rinaningsih (PendIPA Journal of Science Education, 2026)
This study aims to examine the effect of communication skills on students’ learning outcomes through the use of the discussion method in acid–base material. This study is a pre-experimental research using a one-group pretest–posttest design. The results revealed that: (1) the quantity of students’ questioning across three consecutive meetings reached 20.69%, 20.69%, and 37.93%, which were categorized as fairly good. In contrast, the quantity of expressing opinions was 17.24%, 24.14%, and 20.69%, falling into the low category. In terms of quality, students’ questioning skills were classified as good, with percentages of 10.34%, 3.45%, and 3.45%. Likewise, the quality of expressing opinions was also categorized as good, with percentages of 17.24%, 20.69%, and 10.34%. (2) Students’ learning outcomes achieved a classical mastery level of 82.75%. The improvement in learning outcomes was indicated by an average N-gain score of 0.68, which falls into the moderate category. These results indicate that communication skills have an effect on learning outcomes through the implementation of the discussion method in acid–base learning.